DETERMINAN FAKTOR PENYEBAB KEJADIAN PERDARAHAN POST PARTUM KARENA ATONIA UTERI - Purwanti, Sugi; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Most causes of maternal mortality are post-partum hemorrhage. Causes of postpartum hemorrhage is uterine atony with percentage 50-60%, where risk factors include age, high parity, overdistension of uterine . The objective knowing the correlation between maternal age, maternal parity, uterine distension and postpartum hemorrhage due to atonic uterus. The research method was a quantitative survey with case control approach. The population was all postpartum mothers in hospitals Margono Soekarjo in January-December 2014. The population of puerperal women who experience bleeding due to uterine atony of 459 cases. Sample cases were mothers with postpartum hemorrhage due to atonic uterus by 80 respondents and the control sample was normal postpartum mothers by 80 respondents. Univariate analysis used frequency distribution. Bivariate analysis used chi square. Results of the study respondents age risk by 36.2%, parity amounted to 29.4% of respondents at risk, the risk of uterine overdistension by 12.5%. The correlation between age and parity to hemorrhagic puerpuralis due to atony with p value 0.033 and 0.037. The incorrelation between uterine overdistension to hemorrhagic puerpuralis due to atonic uterus with p value 0.473. Conclusion The rcorrelation between age and parity against hemorrhagic puerpuralis due to uterine atony. Puerperal women with risky age had 2.1 greater risk of experiencing hemorrhagic puerpuralis due to uterine atony. Puerperal women with risk parity had 2.2 greater risk of experiencing hemorrhagic puerpuralis due to uterine atony. The incorrelation between uterine overdistension to hemorrhagic puerpuralis due to atonic uterus Keywords: Haemoragic post partum, atony uterine